A metodologia BIM enquanto ferramenta no projecto de arquitectura - Paulo Alberto Peixoto Ferreira (2015)
Architectural representation tools and methods influence the way architecture is thought and created. The same way Industrialization and Modernism changed our buildings, the Information Age we live in will too shape the way we design, manufacture and build. As a result of the contemporary need to design buildings more efficiently, BIM methodology is being increasingly adopted. Although its nomenclature is relatively new, some of the concepts behind this way of working are several decades old with strong ties to early days of computation. Despite these ideas being very familiar today, they were achieved through small, successive discoveries. Thus, this thesis exploits how the initial concepts have evolved and gave rise to what is now BIM; how it plans to address questions such as the lack of productivity of traditional practices in the construction industry and the need for better integration of the different teams in project design; how to use this methods to achieve more sustainable practices and buildings, to help us reach a faster and more elegant way to a healthier future for the planet. As proof of concept two recent case studies were analyzed in which BIM methodology played a crucial role for different reasons. First, the Helsinki Music Centre, a project developed through traditional methods that had to be redesigned with BIM because it exceeded the budget; and second the Manchester Central Library, the refurbishment of a listed building in which all changed had to go through English Heritage for approval. Lastly, we take a look at what may be the future of this methodology and concept of buildings with information if applied on a larger scale, to our streets, neighborhoods and cities.